Ukraine’s experience in resolving the Balkan conflict - Ruda, Viktoriia V. (Linguistics and Culture Review, 2021)
The development of a common foreign policy course and the creation of joint defence have become the main tasks of the European Community from the very beginning of its foundation, and the practical implementation of cooperation in these areas turns out to be rather difficult and runs into certain problems. Being part of the European Community, the member countries are aware of the necessity to pursue such a course in order to obtain the status of a full-fledged subject of international politics, but this does not deprive them of their fears about the loss of their national sovereignty and some foreign policy priorities. The purpose of the study is to study the process of formation and development of cooperation between Western European countries in the field of foreign policy, security and defence, as well as using the experience of the countries of the former Republic of Yugoslavia to resolve the situation on the territory of Ukraine. The comparative approach of peripheral areas emphasises the unsettled situation, which in some cases may seem better than internationally structured and is on the path of consolidation, while in other cases destabilization still strongly affects the development prospects of states.